Genetic Relationships Between Olive (Olea europaea L.) Cultivars And Promissory Genotypes in Catamarca, Argentina - Torres, Laura E (2014)
The study of olive (Olea europea L.) genetic variability is important for the design of plant breeding programs. In Argentina, as in other regions of the world, there are local genetic materials with high agronomic value with unknown origin. The objective of this work was to determine the genetic similarity between olive cultivars of regional interest and local genotypes that had been selected based on their industrial aptitude, in Andalgalá (An) and Pomán (Po) departments (Catamarca province, Argentina). DNA was extracted from 16 local genotypes and from 13 reference cultivars which are currently grown in the region. Seven microsatellites were amplified, including 5 from the DCA series (3, 5, 14, 16, 18), IAS-OLI (27) and UDO (43). PCR products were resolved on a 15% acrylamide bisacrylamide gel and visualized under UV light. Euclidean and Roger’s genetic distances between the genotypes and the reference cultivars were calculated and for each genotype the most similar cultivars were identified. Additionally, we performed a Principal Components Analysis based on the allelic frequencies and results were displayed on a Biplot in order to visualize the genetic relationships between all individuals. In general, genotypes were genetically more similar among them than in relation to the reference cultivars. Genotypes from the local Arauco group showed the lowest genetic distances and the genotype 24SPO presented the highest similarity to a group of reference cultivars. The 44 genotype was the only one that showed the highest similarity to a unique reference cultivar (‘Frantoio’, Mendoza Collection). These results contribute to our knowledge of olive genetic variability, in particular of the materials present in Catamarca Province which are used in genetic improvement programs, suggesting that most genotypes are genetically more related to cultivars of local origin.